Analisis Hermeneutika Kiai Ahmad Yasin Asmuni: Studi Q.S. Al-Nisa’ Dalam Tafsir Ma Asabak - Moh Hasan Fauzi (Al-Adabiya: Jurnal Kebudayaan dan Keagamaan, 2018)
This article would like to see how far the work of Kiai Ahmmad Yasin Asmuni, Tafsir Ma Asabak. Kiai Yasin is one of productive man about the Arabic work and its meaning. In this case, he was a poiner of the meaningful yellow book. The researcher is going to focus about how Kiai Yasin arranged Tafsir Ma> As}a>bak. What this work was pure of his thought or only took from other works. How far his understanding about ulumul qur’an in his work. What he did something contextually in his work. Those questions what are going to explain in this article. Finally, researcher found pro and contra on the publication of Kiai Yasin’s works, there is a little bit different understanding than before and theological substance was strong. On making this researcher is going to use hermeneutic analysis to explore it.